2022
DOI: 10.1002/crq.21345
|View full text |Cite
|
Sign up to set email alerts
|

Perceived and ideal conflict cultures in academe: Creating the conflict cultures survey

Abstract: Focusing on conflict at the organizational level, this study explores Conflict Culture Theory by (a) conceptualizing perceived and ideal conflict cultures, (b) creating and implementing the Conflict Cultures Survey, and (c) testing Gelfand, Leslie and Keller's (2008) proposed two‐dimensional model. Tenured and tenure‐track faculty at a large, American university (N = 346) completed the survey. Ideal conflict cultures varied little whereas perceived conflict cultures varied across departments, suggesting that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Cai and Fink (2002) found that individuals preferred integrating regardless of individualism-collectivism. The study of college professors found nearly no variation in ideal conflict cultures; participants all preferred active and agreeable conflict cultures (Desrayaud, 2022). While this does not suggest that all cultures use active and agreeable strategies uniformly, it does suggest the possibility for universality in ideal conflict cultures:…”
Section: Collectivismmentioning
confidence: 91%
See 4 more Smart Citations
“…Cai and Fink (2002) found that individuals preferred integrating regardless of individualism-collectivism. The study of college professors found nearly no variation in ideal conflict cultures; participants all preferred active and agreeable conflict cultures (Desrayaud, 2022). While this does not suggest that all cultures use active and agreeable strategies uniformly, it does suggest the possibility for universality in ideal conflict cultures:…”
Section: Collectivismmentioning
confidence: 91%
“…The theory of conflict cultures proposes that organizations create and reify expectations for how conflict ought to be handled (Gelfand et al , 2008). Conflict cultures vary along Van de Vliert and Euwema’s (1994) two conflict dimensions – active-passive and agreeable-disagreeable (Desrayaud, 2022; Gelfand et al , 2008). Active conflict cultures value participation, active involvement and open discourse about incompatible goals or ideas, normalizing behaviors such as openly discussing, confronting and forcing conversations.…”
Section: Conflict Culturesmentioning
confidence: 99%
See 3 more Smart Citations